Navarixin alleviates cardiac remodeling after myocardial infarction by decreasing neutrophil infiltration and the inflammatory response - Hu, Peikun; Liu, Wei; Huang, Jungang; Su, Yangfan; Jiang, Huiqi; Wu, Qinyu; Tao, Jun; Liang, Shi; Lin, Jun; Zheng, Junmeng (Frontiers in Pharmacology, 2025)
Coronary atherosclerotic heart disease is an important, worldwide burden on human health. Central muscle infarction is the most dangerous condition, has the highest mortality and disability rates, and is gradually becoming more common among young people. After myocardial infarction, neutrophils recruited to the infarcted area promote the myocardial inflammatory response by releasing proinflammatory factors and chemokines and release matrix metalloproteinases and myeloperoxidases that degrade the extracellular matrix and produce reactive oxygen species, resulting in irreversible myocardial damage and thereby promoting ventricular remodeling. In this study, we constructed a mouse model of myocardial infarction and utilized the CXCR2 receptor inhibitor navarixin (Nav) to reduce neutrophil recruitment after MI. We observed that Nav improved cardiac function, reduced myocardial damage, reduced neutrophil infiltration, reduced inflammatory factor expression and improved cardiac fibrosis in mice. Through transcriptomic analysis, we found that Nav affects signaling pathways such as the innate immune response and the chemokine signaling pathway, thereby decreasing the inflammatory response by reducing neutrophil chemotaxis. This study provides new insights for the use of CXCR2 inhibitors as new therapeutic options for myocardial infarction in the future.